Quassinoids isolated from Brucea javanica inhibit pepper mottle virus in pepper - Ryu, Seung Mok; Kwon, Jaeyoung; Seo, Young Hye; Song, Eun Gyeong; Hong, Seong Su; Kim, Beom Seok; Hong, Jin Sung; Ryu, Ki Hyun; Lee, Dongho (ELSEVIER SCIENCE BV, 2017)
A green fluorescent protein (GFP)-tagged pepper mottle virus (PepMoV) based leaf-disc method and systemic host method were developed to identify antiviral agents. Preliminary experiments using a PepMoV-GFP based leaf-disc method led to the isolation of five quassinoids, including brusatol (1), bruceantin (2), brucein A (3), bruceantinol (4), and brucein B (5), from the CH3OH extract of Brucea javanica. All isolated compounds exhibited inactivation effects in systemic host plants, and compounds 3 and 4 were potent, with a minimum inhibitory concentration of 10 M. Furthermore, compound 3 was found to have a protective effect at the tested concentration of 40 M. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: MOSAIC-VIRUS; STRUCTURAL ELUCIDATION; AGENTS; SEEDS